Surgical Extraction of Mandibular Third Molars: Risk Assessment and Predictable Complexity - Shembesh, Hisham (Khalij-Libya Journal of Dental and Medical Research, 2024)
Objective. The study aims to develop and validate new practical and simple but robust index to determine the complexity level of surgical extraction of mandibular third molars (MTM). Methods. A cross-sectional study with sample of 100 patients referred for management of MTM. Complexity index scores recorded twice at 6 weeks intervals preoperatively by oral and maxillofacial specialist. Prediction of the surgical difficulty and the degree of agreement of different variable indexes were calculated. Results. Out of 100, 78 patients with 139 impacted MTM, 26 were males and 52 were female, with a mean age of 26.40±6.39 years (range, 18-45 years). The prediction of operative difficulty was significant as measured by impaction angulation, distance to ramus, and impaction depth. Most cases were classified as complexity level II (63 [80%]). Although only 3 out of 100 cases (4%) were classified as complexity level III. There was no significant difference in age based on the gender (male: 27.54±7.35 years, female: 25.83±5.86 years; P=0.268). Conclusion. Using MTM complexity index as a preoperative tool to evaluate the surgical difficulty, including different patient-specific variables could facilitate treatment planning, help prevent complications and assess the possibility of referral. الاهداف. تهدف الدراسة إلى تطوير والتحقق من صحة مؤشر عملي وبسيط ولكن قوي لتحديد مستوى تعقيد الاستخراج الجراحي للأضراس الثالثة الفك السفلي (MTM) طرق الدراسة. دراسة مقطعية مع عينة من 100 مريض تمت إحالتهم لإدارة MTM. تم تسجيل درجات مؤشر التعقيد مرتين على فترات كل 6 أسابيع قبل الجراحة من قبل أخصائي الفم والوجه والفكين. تم حساب التنبؤ بالصعوبة الجراحية ودرجة اتفاق المؤشرات المتغيرة المختلفة. النتائج. من بين 100، كان هناك 78 مريضًا مصابًا بـ 139 MTM، 26 ذكرًا و52 أنثى، بمتوسط عمر 26.40 ± 6.39 سنة (المدى 18-45 سنة). وكان التنبؤ بصعوبة المنطوق كبيرا كما تم قياسه عن طريق التزوي الانحشار، والمسافة إلى الفرع، وعمق الانحشار. تم تصنيف معظم الحالات على أنها مستوى التعقيد الثاني (63 [80٪]). على الرغم من أن 3 فقط من أصل 100 حالة (4٪) تم تصنيفها على أنها مستوى التعقيد الثالث. لم يكن هناك اختلاف كبير في العمر على أساس الجنس (الذكور: 27.54 ± 7.35 سنة، الإناث: 25.83 ± 5.86 سنة؛ P = 0.268). الاستنتاج. استخدام مؤشر تعقيد MTM كأداة قبل الجراحة لتقييم الصعوبة الجراحية، بما في ذلك المتغيرات المختلفة الخاصة بالمريض يمكن أن يسهل تخطيط العلاج، ويساعد على منع المضاعفات وتقييم إمكانية الإحالة